(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Globally, females including girl children are at higher risk of social abuse, poverty, and violence than males. They are more malnourished, deprived, and less likely to be educated than males of the same socio-economic environment. Moreover, in comparison to their male counterparts, females with the same qualifications and experiences are less likely to own businesses or be in higher managerial positions. In the corporate world, females earn 75 percent less than males. The aim of this research work is to contribute to a better understanding of the role of social entrepreneurship and the importance of it in empowering women in India. Just due to the lower status in society, the entrepreneurial ability of women in India is still unrecognized or ignored. Women in rural India are considered the most vulnerable groups exposed to high risk of malnutrition, poverty, and social exclusion. Although, a relatively new concept and new observable fact, social entrepreneurship has already depicted its capacity in addressing the needs of marginalized social groups and has emerged as a model that might contribute significantly to the women empowerment that is the needs of the hour. This paper focuses on the importance of exploring women’s entrepreneurial capacity to the socio-economic background of the country and the basic problems that women entrepreneurs face in India.